Prospects for offshore hydrogen production in the Netherlands - Joost van Stralen; Gaby Janssen; Joris Koornneef; Martin Scheepers; Jeffrey Sipma; Bob van der Zwaan (Environmental Research: Energy, 2025)
Using a technology-rich optimization model for the Netherlands, we analyse the potential role of offshore energy options for system integration purposes. Our focus is on offshore hydrogen production produced by wind power in the Dutch Exclusive Economic Zone of the North Sea. We conclude that large-scale offshore green hydrogen development is a robust outcome of our scenarios. We also find that offshore green hydrogen production dominates over onshore hydrogen generation with green electricity delivered to shore through power lines in the North Sea. The main reason is the avoidance of elevated costs associated with a high voltage electricity grid at sea. We observe a large range of possible offshore hydrogen production levels, from 40 to 250 TWh yr ^−1 in 2050, depending e.g. on the level of total hydrogen demand, the availability of competing emission abatement options, and the offshore wind energy potential. After 2040 it becomes optimal to transport most energy from newly installed offshore wind capacity to shore in the form of hydrogen. Because of the long lead times involved in infrastructure planning, offshore hydrogen production and transportation should be put high on political and industrial agendas.